Lokal Dalam Menciptakan Perlindungan Dan Pengelolaan Bagi Lingkungan Hidup - Yudhi Priyo Amboro (Fakultas Hukum, Universitas Internasional Batam, 2016)
The local wisdom become an issue since Act No. 32 Year 2009 introduced the local wisdom as a part of principle for public policy on environment. Some questions appear when local government wanted to issue public policy related with the environment and make a connection to the local wisdom. It is still questionable concerning what the local wisdom is. This writing tries to pierce those questions in a perspective of legal theology, with a legal research method.